Elemen-elemen Politik sebagai Strategi Mengkapitalisasi Perilaku Pemilih dalam Kontestasi Pemilu Presiden tahun 2024 di Indonesia - Febriali Sahl, Dafiq; Mauluddin, Agus (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2024)
This year’s Presidential and Vice-Presidential election is a political power struggle that will determine the future of the Indonesian nation. This qualitative research aims to assess electoral politics, specifically the electability of each candidate pair based on key political elements. The research method used is a literature review, with secondary data obtained from journal articles, books, and online sources. The results of the study indicate that trends in candidate electability can be measured through the harmonization of political survey results and the configuration of each candidate’s electability. The candidate pairs incorporate political elements such as identity politics, political blunders, work programs, elite or key actors, public gimmicks and sensationalism, and political maneuvers, as seen in the campaigns of Anies-Muhaimin, Prabowo-Gibran, and Ganjar-Mahfud. These political elements, which have long existed in Indonesia’s political arena (conventional elements), often dramatically shift the electoral strength of each camp. The candidates must manage these political elements to their electoral advantage if they wish to increase their electability and win the election. This study examines the strategy of capitalizing on voter behavior in the 2024 Presidential Election.